Serum Zinc, Calcium, Vitamin D and Ferritin level in Chronic Telogen Effluvium Among Women in Mosul: A Case- Control Study - F.K. Alamory, Nagham; M.M. Alsabaawy, Osama; AH. Jasim, Shaymaa; B. Fathi, Haitham (Public Health of Indonesia, 2025)
Background: Investigation into the role of nutrient factors in alopecia is an exciting and expanding field. Despite the vast amount of evidence, their conclusions are conflicting. Objectives: to estimate the differences in micronutrients (zinc, calcium, vitamin D and ferritin) between women with chronic telogen effluvium and healthy alopecia-free women. Methods: Thirty age-matched healthy women and thirty telogen effluvium female patients were recruited from a private dermatology clinic in Mosul for this case-control research. To measure the zinc, calcium, vitamin D and ferritin, ten milliliters of blood were extracted. The independent two sample t-test was applied to examine the groups' differences of these nutrient factors. Results: TE patients had a zinc level of 60.78±28.79 µg/dl, which was 17.78 g/dl lower than the alopecia-free control group (95% CI of the Difference: 5.16 to 30.39 mg/dl) (p = 0.01). The patient group's calcium was 8.56±0.28 mg/dl, compared to 9.36±0.59 mg/dl in the control group. This difference was statistically significant (p<0.0001). The vitamin D levels of both the healthy control group and the TE patients were found to be 41.56±13.26 g/ml and 14.97±8.56 g/ml, respectively. This difference was statistically significant (p =0.01). Ferritin levels were 29.75±31.02 ng/ml in the sick group and 47.33±26.84 ng/ml in a control group. The alopecia group's average ferritin was 17.57 ng/ml less than that of the normal group, and this difference was statistically significant (p =0.02). Conclusions: Monitoring and restoration of hair follicle micronutrients (Zinc, Calcium, Vitamin D & Ferritin) is an important step in the management of women with diffuse chronic TE. Keywords: Telogen effluvium; Zinc; Calcium; Vitamin D; Ferritin